Nivel de conocimiento sobre Alimentación y practicas alimentarias en madres de preescolares - Ferrel García, Cinthia Judith (2016)
Quantitative research descriptive correlational and cross-sectional, was conducted to determine the relationship between the level of knowledge about feeding and food practices in mothers of preschool in the Barrio 6 of the Alto Trujillo-El Porvenir, 2016. The sample consisted of 60 selected mothers according to inclusion criteria, who were administered surveys Level of Knowledge about feeding and food practices developed by the researchers. Independence Test Criteria Chi-Square was used to determine the relationship between variables. The results were: 36.7 percent of mothers had a medium knowledge level, the same presented a low level; and 26.7 percent, a higher level. As for food practices had 80 percent and 20 percent adequate, inadequate practices. Concluding that there is significant relationship between the level of knowledge and food practices in mothers who participated in the study. Keywords: Knowledge, Food Practices, Preschoolers